Reconsidering 'virtuous circle' and 'media malaise' theories of the media: An 11-nation study. (October 2014) - Curran, James; Coen, Sharon; Soroka, Stuart; Aalberg, Toril; Hayashi, Kaori; Hichy, Zira; Iyengar, Shanto; Jones, Paul; Mazzoleni, Gianpietro; Papathanassopoulos, Stylianos; Rhee, June Woong; Rojas, Hernando; et al.
This study, based on a content analysis of television news and survey in eleven nations, explores the split between those who see the media as politically alienating and others who see the media as encouraging greater political involvement. Here, we suggest that both positions are partly right. On the one hand, television news, and in particular public service television news, can be very effective in imparting information about public affairs and promoting a culture of democracy in which news exposure, public affairs knowledge, sense of democratic competence and political interest feed off each other. On the other hand, the views represented in public affairs news are overwhelmingly those of men and elites, which can discourage identification with public life.